Availability and Quality of Family Planning Services in the Democratic Republic of the Congo: High Potential for Improvement - Mpunga, Dieudonné (Glob Health Sci Pract, 2017)
OBJECTIVE: To determine the availability and quality of family planning services within health facilities throughout the Democratic Republic of the Congo (DRC). METHODS: Data were collected for the cross-sectional study from April 2014 to June 2014 by the Ministry of Public Health. A total of 1,568 health facilities that reported data to the National Health Information System were selected by multistage random sampling in the 11 provinces of the DRC existing at that time. Data were collected through interviews, document review, and direct observation. Two dependent variables were measured: availability of family planning services (consisting of a room for services, staff assigned to family planning, and evidence of client use of family planning) and quality of family planning services (assessed as “high” if the facility had at least 1 trained staff member, family planning service delivery guidelines, at least 3 types of methods, and a sphygmomanometer, or “low” if the facility did not meet any of these 4 criteria). Pearson's chi-square test and odds ratios (ORs) were used to test for significant associations, using the alpha significance level of .05. RESULTS: We successfully surveyed 1,555 facilities (99.2%) of those included in the sample. One in every 3 facilities (33%) offered family planning services as assessed by the index of availability, of which 20% met all 4 criteria for providing high-quality services. Availability was greatest at the highest level of the health system (hospitals) and decreased incrementally with each health system level, with disparities between provinces and urban and rural areas. Facilities in urban areas were more likely than in rural areas to meet the standard for high-quality services (P<.001). Public facilities were less likely than private facilities to have high-quality services (P=.02). Among all 1,555 facilities surveyed, 14% had at least 3 types of methods available at the time of the survey; the most widely available methods were male condoms, combined oral contraceptive pills, and progestin-only injectable contraceptives. CONCLUSION: Availability and quality of family planning services in health facilities in the DRC remain low, with inequitable distribution of services throughout the country. To improve access to and use of family planning, efforts should focus on improving availability and quality at lower health system levels and in rural areas where the majority of the population lives.